BECOMING AN IDEAL PERSON TODAY: A COMPARATIVE ANALYSIS OF ABDUL KARIM AL-JILI'S AND JEAN PIAGET'S THOUGHT ON THE PERFECT HUMAN - Reza Wasilul Umam (UIN Kiai Haji Achmad Siddiq Jember, 2023)
Research on Islamic studies will always continue and will continue to grow. This paper compares Abdul Karim al-Jili's and Jean Piaget's thoughts on the perfect human, especially in the tasawwuf. Al-Jili divides the levels insan kamil into three stages: al-bidayah, at-tawasuth, and al-khitam. From each step of becoming an ideal person, there is a part of the stage that humans must go through mujahadah, riyadoh, ma’rifat, mortal', musyafah, and musahadah. Meanwhile, to achieve Piaget's theory emphasizes the learning process according to the pattern of individual cognitive development stages. According to Piaget, the learning process consists of three steps: assimilation, accommodation, and equilibration. In practice, there are at least six methods applied in shaping human behavior: right ways (uswah hashanah), training and habituation, taking lessons (ibrah), advice (mau’idzah), discipline, and independence.